Implementation of Local Wisdom of Minang Culture (Studies Of The Minang Diaspora in Surabaya) - Yosi Trisa; Agus Suprijono; M Jacky (Universitas Negeri Surabaya, 2019)
The aim of the study was to understand how the application of Minang Culture Local Wisdom values